Demand-Side Financing Transformation: Formulating Indexed Scholarship Unit Costs for Inclusive SMA Unggul Garuda - Mohamad Ichsan (STIE AMKOP, 2026)
This study formulates an indexed scholarship unit-cost framework for SMA Unggul Garuda, an affirmative secondary education program relying on the Indonesia Endowment Fund for Education (LPDP). The transition to demand-side financing reveals critical policy gaps in the national input cost standards (SBM), including the absence of secondary education tuition nomenclature, uniform national nutritional allowances ignoring regional price disparities, and exclusionary reimbursement-based transportation mechanisms. Using a qualitative policy study approach, three policy alternatives were evaluated based on William Dunn's criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The analysis concludes that standardizing financing through generic national regulations is administratively inefficient. Instead, this paper recommends enacting a specific Other Input Cost Standards (SBML) package. This tailored intervention ensures legally binding tuition fees, regionally indexed living allowances, and centralized zero-cost transportation, effectively securing the program's inclusivity and long-term sustainability. Kata kunci: Education Financing, Demand-Side Financing, Endowment Fund, Policy Analysis, Unit Cost.